PENGARUH VISKOSITAS OLI TERHADAP KEKERASAN DAN STRUKTUR MIKRO BAJA 60 - Noor Setyo (Wahana Ilmuwan, 2016)
This study aims to determine the effect of cooling medium in the quenching process on the level of the surface hardness of steel alloy ST 60 has a composition of 0.45% C, 0.33% Si; 0.43% Mn. While as the cooling medium varisi sequentially used oil SAE 20; SAE 40; and SAE 60. Quenching heating process is done by heating the steel in the furnace heated to a temperature of austenite 7500C, being the quenching process is performed by using the oil cooler media SAE10; SAE 40; and SAE 80. The surface hardness before and after quenching is known to test the micro Vickers on a load of 150 grams, while the microstructure observation was performed using an optical microscope magnification of 200 x.Results showed a linear relationship between the level of violence to the level of dilution oil cooler. Material surface hardness increased with the increasing rate of the cooling medium viscosity. Sequentially large surface hardness of the thinned oil SAE 10; SAE 40; and SAE 80 is obtained 175VHN0,015; 179 VHN0,15; dan 195VHN0,015. The microstructure of the experience was change of pearlite into cementite with a higher level of dilution cooling medium.